PENGARUH PERUBAHAN LABA BERSIH, PERUBAHAN LABA KOMPREHENSIF, DAN PERUBAHAN PERINGKAT OBLIGASI TERHADAP RETURN SAHAM - Triani Sri Rejeki; Yusni Warastuti (Universitas Katolik Soegijapranata Semarang, 2012)
This study aims to investigate the influence of financial statements information that is the change in net income and comprehensive income and changes in bond ratings information on stock returns. The study was conducted for all companies listed on the Stock Exchange and are doing the rating of bonds in the period 2002-2008. Results of this study was change in net income is not a positive influence on stock returns, while changes in comprehensive income and changes in bond ratings a positive effect on stock returns.